Communications of smart systems based on software-defined radio and internet of things - Jaloudi, Samer (Edelweiss Applied Science and Technology, 2025)
The Internet of Things (IoT) concept has many applications in smart systems, such as smart homes, smart cities, and smart healthcare systems. Many IoT-based systems have three layers: the things, the fog, and the cloud. IoT-based systems depend on a wireless telecommunication protocol to exchange data with sensors and actuators in the things layer. Bluetooth, Bluetooth Low Energy (BLE), Zigbee, and WiFi are examples of such protocols. These protocols use diverse and different transmit and receive modules that depend on a specific frequency. The challenge is to use a single, power-efficient, moderate-cost platform for the reception of wireless signals of these protocols in the fog layer and to work with the gateway’s protocol for interoperability. The software-defined radio (SDR) is a reconfigurable radio frequency (RF) platform that can serve as a multi-frequency receiver. This research proposes in the fog layer an SDR platform and a gateway that receives data from this platform, reformats it into JavaScript Object Notation (JSON) to achieve interoperability, and transfers the information over HTTP(S) to online servers in the cloud layer. The developed system is moderate-cost, power-efficient, easy to set up, interoperable, and can be used for all IoT-based smart systems that follow the three-layer architecture.